Photosynthetic bacteria with iron oxide nanoparticles as catalyst for cooking oil removal and valuable products recovery with heavy metal co-contamination - Chaiyarat, Anuwat (Waste management (New York, N.Y.), 2022)
Copyright © 2022 Elsevier Ltd. All rights reserved.